Evaluasi Layanan Jasa di Pusat Pemotongan Hewan di Banyumelek, Kabupaten Lombok Barat: Evaluation of Services at Slaughtering Center in Banyumelek, West Lombok Regency - Setiawan, Risqi Firdaus; Fitriana, Nisa Hafi Idhoh (Jurnal Ilmiah Manajemen Agribisnis, 2023)
This study aims to analyze the suitability of service activity activities with the Standard Operating Procedure (SOP) to analyze the influence of infrastructure, professionalism of workers, and speed of service on service quality according to service users, as well as formulate efforts to improve service quality at RPH Banyumulek, West Lombok Regency. The data used in this study are primary data from field observations and interviews with the help of questionnaires and secondary data from Banyumulek RPH and other studies. The samples used were 30 service users. Methods of analysis using descriptive qualitative and SEM-PLS. The results showed that 88.9% of service activities were by the SOP, so they were at a high level of compliance. Of the three variables analyzed, infrastructure and service speed positively and significantly affect the service quality of Banyumulek RPH services. Meanwhile, the variable of worker professionalism has no significant impact on service quality according to service users.